2018
DOI: 10.29312/remexca.v4i1.1264
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad del lodo textil en la producción y composición química del fruto de tomate

Abstract: those permitted by the environmental and health standards. However, we detected the presence of helminth eggs in higher values than those allowed by the standard in the fruits of plants treated with the highest concentration of sludge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…Even if potassium was generally low, the highest concentration was found in inflorescences, leaves and stems, but in root this effect was not observed. In stem, potassium content increased in proportion to the concentration of sludge in the substrate, which seems to indicate that the sludge promotes the absorption of potassium, even when, in previous studies low levels of potassium are reported in this type sludge (Narváez et al, 2013). Also, the reports from the literature show that sludge affects in different ways nutrient uptake by plants, for example, it is reported that the addition of sludge decreased Ca concentration in tobacco leaves (Kabata and Pendias, 1992) and in tomato fruits (Narvaez-Ortiz et al, 2013).…”
Section: Absorption Of Mineral Nutrientsmentioning
confidence: 70%
See 2 more Smart Citations
“…Even if potassium was generally low, the highest concentration was found in inflorescences, leaves and stems, but in root this effect was not observed. In stem, potassium content increased in proportion to the concentration of sludge in the substrate, which seems to indicate that the sludge promotes the absorption of potassium, even when, in previous studies low levels of potassium are reported in this type sludge (Narváez et al, 2013). Also, the reports from the literature show that sludge affects in different ways nutrient uptake by plants, for example, it is reported that the addition of sludge decreased Ca concentration in tobacco leaves (Kabata and Pendias, 1992) and in tomato fruits (Narvaez-Ortiz et al, 2013).…”
Section: Absorption Of Mineral Nutrientsmentioning
confidence: 70%
“…The incorporation of sludge to more than 10% increases electrical conductivity and pH of effluent and decreases crop development. In production of potted hydrangea the en este tipo de lodos (Narváez et al, 2013). Asimismo, los reportes en la literatura muestran que los lodos afectan de forma diferente a la absorción de nutrimentos por las plantas, por ejemplo, se reporta que la adición de lodos disminuyó la concentración de Ca en hojas de tabaco (Kabata y Pendias, 1992) y en frutos de tomate (Narvaéz-Ortiz et al, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation